Antifungal activity of silver nanoparticles in combination with ketoconazole against Malassezia furfur - Mussin, Javier Esteban (2019)
Fil: Mussin, Javier Esteban. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.